PENGARUH PARITAS DAN RIWAYAT PENGGUNAAN KB HORMONAL TERHADAP KEJADIAN KANKER PAYUDARA DI RSU DADI KELUARGA PURWOKERTO - Prabandari, Fitria; Fajarsari, Dyah (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Breast cancer is a malignancy derived from gland cells, glandular channels and breast support tissue, excluding the breast skin. The etiology of breast cancer can not be explained. However, many studies have shown that there are several factors that are associated with an increased risk or the likelihood of breast cancer. at the General Hospital of Dadi Family Purwokerto because of increased incidence of breast cancer from January to October 2014 a number of 2,320 cases of breast cancer. This study used a restropective case control approach. Data analysis using non-statistical analysis or referred to as a simple statistical analysis. To test the hypothesis about the relationship between two variables used Chi Square. There is a parity relationship with the incidence of breast cancer in RSU Dadi Family Purwokerto. There is correlation of hormonal hormonal use factor with incidence of breast cancer in RSU Dadi Keluarga Purwokerto. Keywords: Breast Cancer, Parity, History of Hormonal Family Use